Hypochlorous acid in ophthalmology: a narrative review - Mordarska, Milena; Łozowski, Jan; Gołąbek, Natalia; Szymański, Łukasz; Merc, Artur; Piątek, Przemysław; Kodura, Alicja; Piwowarczyk, Alicja; Paluchowska, Joanna; Białas, Julia (Quality in Sport, 2026)
Background: Hypochlorous acid (HOCl) is a naturally occurring molecule that plays a key role in host defence, exhibiting broad-spectrum antimicrobial activity against bacteria, viruses and fungi while maintaining an excellent safety profile for human tissues. Its utility has been demonstrated in numerous studies in wound care, perioperative antisepsis and more recently in nasopharyngeal sprays and inhalation applications. Aim: The purpose of this study was to provide an overview of the current and potential uses of hypochlorous acid in ophthalmic practice. Materials and methods: A comprehensive narrative review of the literature was conducted using the PubMed, Web of Science, ResearchGate, Google Scholar, Scopus and Embase databases. The search strategy was based on the following combination of key terms: (“hypochlorous acid” OR HOCl) AND (ophthalmology OR keratitis OR “ocular surgery” OR “meibomian gland dysfunction” OR “dry eye” OR blepharitis OR ocular OR “ocular surface” OR “eye infections” OR conjunctivitis). Results: HOCl demonstrated broad antimicrobial activity in several studies, with meaningful reductions in bacterial load, rapid in vitro fungicidal effects and improvement in clinical parameters of blepharitis, dry eye disease and meibomian gland dysfunction. Antiseptic efficacy relative to povidone-iodine varied, with some studies showing inferior perioperative performance. Across all reports, HOCl was well tolerated, with no serious adverse events and consistently better patient comfort than povidone-iodine. Conclusions: Hypochlorous acid is a safe, well-tolerated antiseptic with potential benefits in eyelid hygiene, dry eye disease, blepharitis and as an adjunct in ocular infections. While its antimicrobial efficacy is promising, it is inconsistent compared with povidone-iodine and it should currently be viewed as a complementary rather than a replacement agent. Further standardized clinical studies are needed to clarify its optimal role.